Substratum and temperature requirement for germination of satawar (Asparagus racemosus) seed - VIJAY LAXMI; R.S. VERMA; OMVATI VERMA (Seed Research, 2026)
Asparagus racemosus, an important medicinal herb, can be propagated through seed as well as crowns (roots), but propagation through crowns is not recommended, as roots are the economic part. Seed testing protocols are also not available for medicinal plants; hence, the present investigation was carried out to work out suitable substratum and optimum temperature requirement for satawar seed germination testing. Among five substrata, 'top of the paper' and 'between the paper' were at par with each other and significantly superior to 'rolled towel papers', 'soil' and 'sand' for conducting standard germination test. Final germination percentage was non-significantly influenced by temperature, but seedling vigour parameters were significantly higher at 20°C. At 20°C temperature, germination value, speed of germination, mean germination time and days taken to initiate germination, fifty percent (T5) and eighty per cent (T) germination were significantly higher than that at 25°, 30° and 35°C temperatures.